Effect of activity restriction due to the COVID-19 pandemic on the physical measurements of Japanese top-level athletes - Takahashi, S.; Sasadai, J.; Shimizu, R.; Suzuki, A.; Takashima, N.; Hotta, Y.; Kukuchi, S.; Fukami, K.; Nakajima, K.; Okuwaki, T. (Journal of High Performance Sport, 2022)
In order to investigate the effect of sports activities restriction during the COVID-19 pandemic on physical function among athletes, this study compared the physical measurements of athletes from immediately after lifting the restriction of activities with their measurements after returning to competition. The subjects were twenty-nine Japanese top-level athletes (male: 14, female: 15). Measurements of the upper limbs, trunk, and lower limbs were performed from the viewpoint of injury prevention. The results showed that in female athletes, the upper limb functions of external rotation at maximum elevation and scapular adduction, and lower limb muscle power and muscle mass were significantly improved after returning to competition compared to immediately after the lifting of restrictions. There was no significant difference observed in the trunk measurements of both male and female athletes. In the future, these results will be useful in conditioning athletes if sports activities are once again restricted.